Minilaparoscopy vs. standard laparoscopic donor nephrectomy: compari¬son of safety, efficacy and cosmetic outcomes in a randomized clinical trial. - Simforoosh, Nasser; Hosseini Sharifi, Seyed Hossein; Valipour, Reza; Narouie, Behzad; Kamranmanesh, Mohammad Reza; Soltani, Mohammad Hossein (Urology Journal, 2015)
Purpose: This study was conducted to compare safety, efficacy and cosmetic outcome between standard laparoscopic live donor nephrectomy (sLDN) and mini-laparoscopic donor nephrectomy (mLDN) in a randomized clinical trial. Materials and Methods: From March 2012 to June 2013, 100 consecutive kidney donors were randomly assigned to two equal groups for laparoscopic donor nephrectomy. mLDN: Six to eight centimeters Pfannenstiel incision was made slightly above pubis symphysis and 11 millimeters trocar was fixed through exposed fascia using open technique. Five mm port was placed under direct vision at the umbilicus for camera insertion and two 3.5 mm ports were placed in subxiphoid and paraumbilical area. sLDN: Ten mm port was placed at umbilicus using open access technique for camera insertion. Five mm trocar for grasping and 11 mm trocar for vascular clipping were placed at subxiphoid and paraumbilical areas under direct vision, respectively. The second 5 mm trocar was placed in suprapubic area. Cosmetic appearance was assessed three months after surgery by using the Patient Scar Assessment Questionnaire (PSAQ). Results: Demographic data of the patients was not significantly different between two groups. Total operative time and ischemic time was nearly similar in both groups (104 ± 21 vs. 114 ± 24 min; P = .327 and 4.03 vs. 4.07 min; P = .592). There were no cases of conversion to open surgery. Mean hospital stay was similar between the two groups [2.1 (2-5) vs. 2.4 (2-5) days; P = .346]. Kidney graft function assessed by serum creatinine values (mg/dL) of recipients, was equivalent in both groups (1.58 vs. 1.86: P = .206). Mean appearance score (34 vs. 29) and consciousness score (22 vs. 18) in PSAQ showed significantly better results in the mLDN group. Conclusion: Our experience in this study revealed that peri- and post-operative findings were comparable between sLDN and mLDN, but mLDN has significant better cosmetic appearance than standard laparoscopic approach.